2023
DOI: 10.1002/cmdc.202200599
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation and Delivery of an Osteosarcoma Stem Cell Active Gallium(III)‐Diflunisal Complex Using Polymeric Micelles

Abstract: Here we report the encapsulation of an osteosarcoma stem cell (OSC) potent gallium(III)-diflunisal complex 1 into polymeric nanoparticles, and its delivery into osteosarcoma cells. At the optimum feed (20 %, 1 NP 20 ), nanoparticle encapsulation of 1 enhances potency towards bulk osteosarcoma cells and OSCs (cultured in monolayer and three-dimensional systems). Strikingly, the nanoparticle formulation exhibits up to 5645-fold greater potency towards OSCs than frontline anti-osteosarcoma drugs, doxorubicin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Passeri et al investigated to show that PLGA-PEG polymeric micellar NPs can deliver the OS stem cell active gallium (III)-diflunisal complex into OS cells. This NP formulation showed equivalent or superior sarcosphere toxicity due to increased nuclear DNA damage, cyclooxygenase-2 downregulation, and caspase-dependent apoptosis than other anti-OS drugs such as DOXO, Cis, or Salinomycin [71].…”
Section: Organic Nanocarriersmentioning
confidence: 94%
“…Passeri et al investigated to show that PLGA-PEG polymeric micellar NPs can deliver the OS stem cell active gallium (III)-diflunisal complex into OS cells. This NP formulation showed equivalent or superior sarcosphere toxicity due to increased nuclear DNA damage, cyclooxygenase-2 downregulation, and caspase-dependent apoptosis than other anti-OS drugs such as DOXO, Cis, or Salinomycin [71].…”
Section: Organic Nanocarriersmentioning
confidence: 94%
“…For example, PEG–PLGA micelles were used to encapsulate the gallium (III)-diflunisal complex for treating osteosarcoma, and the results showed that the resulting nanoparticle formulations were 5,645 times more potent against osteosarcoma than doxorubicin and cisplatin. The nanoparticle formulation also induced nuclear damage to DNA, downregulation of cyclooxygenase-2, and caspase-driven apoptosis ( Passeri et al, 2023 ).…”
Section: Plga Targeted Nano-drug Delivery Systemsmentioning
confidence: 99%